Plasmonic mode coupling and thin film sensing in metal–insulator–metal structures - Andam, N. (Sci Rep, 2021)
Optical sensors based on surface plasmon resonance (SPR) in the attenuated total reflection (ATR) configuration in layered media have attracted considerable attention over the past decades owing to their ability of label free sensing in biomolecular interaction analysis, and highly sensitive detection of changes in refractive index and thickness, i.e. the optical thickness, of thin film adsorbates (thin film sensing). Furthermore, SPR is highly sensitive to the refractive index of the medium adjacent to the bare metal, and it allows for bulk sensing as well. When deposited at the metal/air interface, an adsorbed layer disturbs the highly localized, i.e. bound, wave at this interface and changes the plasmon resonance to allow for sensing in angular or wavelength interrogation and intensity measurement modes. A high degree of sensitivity is required for precise and efficient sensing, especially for biomolecular interaction analysis for early stage diagnostics; and besides conventional SPR (CSPR), several other configurations have been developed in recent years targeting sensitivity, including long-range SPR (LRSPR) and waveguide-coupled SPR (WGSPR) observed in MIM structures, referred here to by MIM modes, resulting from the coupling of SPRs at I/M interfaces, and Fano-type resonances occurring from broad and sharp modes coupling in layered structures. In our previous research, we demonstrated that MIM is better than CSPR for bulk sensing, and in this paper, we show that CSPR is better than MIM for thin film sensing for thicknesses of the sensing layer (SL) larger than 10 nm. We discuss and compare the sensitivity of CSPR and MIM for thin film sensing by using both experiments and theoretical calculations based on rigorous electromagnetic (EM) theory. We discuss in detail MIM modes coupling and anti-crossing, and we show that when a thin film adsorbate, i.e. a SL), is deposited on top of the outermost-layer of an optimized MIM structure, it modifies the characteristics of the coupled modes of the structure, and it reduces the electric field, both inside the SL and at the SL/air interface, and as a result, it decreases the sensitivity of the MIM versus the CSPR sensor. Our work is of critical importance to plasmonic mode coupling using MIM configurations, as well as to optical bio- and chemical-sensing.